Towards a Good Education in Very Remote Australia: Is it Just a Case of Moving the Desks Around? - Guenther, John; Bat, Melodie (The Australian Journal of Indigenous Education, 2013)
The education system, as it relates to very remote Aboriginal and Torres Strait Islander communities in Australia, faces challenges. While considerable resources have been applied to very remote schools, results in terms of enrolments, attendance and learning outcomes have changed little, despite the effort applied. The Cooperative Research Centre for Remote Economic Participation (CRC-REP) in its Remote Education Systems (RES) project is trying to understand why this might be the case, and also attempting to identify local solutions to the ‘problem’ of very remote education. The RES project is in the process of building its research program across five remote sites in the Northern Territory, South Australia and Western Australia. As the project begins, the researchers involved have begun to consider what are the assumptions behind the ‘system’ in its current form(s). The article begins with an outline of the context of remote education in Australia within a rapidly changing global environment. However, the purpose of the article is to outline many of the assumptions built into remote education and to ask what the alternatives to these assumptions might be. The authors go on to ask questions about how a remote education system would approach some of the assumptions presented. The assumptions presented are based on a reading of the philosophical bases of education. The questions are designed to prompt a deeper discussion about how the values and worldviews of those living in very remote communities might be taken into consideration and acted upon.